Is Your Application Gender Biased? - Ribeiro Lopes, Milena; Vogel, Carl (My University, 2019)
The process of design is underpinned by a solid methodology that comprises stages of research, creation and validation of the ideas in order to ensure that a product or a service will meet the users’ needs. However, in the realm of online dating applications, women reported to have a frustrating experience, marked by sexist remarks and offensive behaviour. When design fails to deliver a good experience and to meet women’s needs, one question rises: are applications biased in the beginning of the design process? This research proposes a method to investigate biases in the design of mobile experiences.
PUBLISHED
Keywords: Mobile applications; Gender biases; Online dating; Design methods; Creative Technologies; Digital Engagement; Digital Humanities; Computational Linguistics; Computational linguistics; DESIGN; DESIGN METHODS & AIDS; GENDER; computational linguistics; gender bias